Enlargement and Exit: The Origins of Article 50 - Martijn Huysmans (Utrecht University, Utrecht University School of Economics (U.S.E.), 2018)
Many international organizations and the vast majority of federations lack exit clauses. Existing theoretical explanations of this stylized fact focus on issues of credible commitment, signaling, and the risk of strategic exploitation. However, such accounts are unable to explain the adoption by the European Union (EU) of Article 50, which allows withdrawal. I theorize and demonstrate empirically that in the case of the EU, an exit-voice logic lies at its origin during the 2002-2003 European Convention. As a protection to undesired policy changes post entry, countries of the 2004 Eastern accession demanded an exit right. Underlying the fear for policy changes was their much lower level of economic development and corresponding differences in policy preferences. As a mirror image, rich outliers like the UK and Denmark also supported Article 50, which likely contributed to its final adoption through the Treaty of Lisbon.
Keywords: 330; European Integration; Withdrawal; Secession; European Union; Enlargement; Exit